The Study of Vehicle Safety Aspects Influencing Malaysian Urban Consumer Car Purchasing Behaviour - Ng Hung; Rashad Yazdanifard (International Journal of Management, Accounting and Economics, 2015)
As the amount of accidents on the road increases in tandem with the increase in the amount of cars on the road every year, vehicle safety aspect now plays the primary role which influences consumer choice when making a new vehicle purchase. In one of the research quoted by Koppel et.al, (2008), the most important aspect which influences a consumer's choice of vehicle was safety. The aim of this study is to fine out: 1) describe the thoughts of Malaysian consumers about the safety level of their vehicle, 2) describe the type of vehicle safety system consumers are putting an emphasize on, and 3) describe what are the top three advanced vehicle safety system preferred in their cars.